Counterfactual explanations for remaining useful life estimation within a Bayesian framework - Andringa, Jilles (2025)
Andringa, J., Baptista, M. L., & Santos, B. F. (2025). Counterfactual explanations for remaining useful life estimation within a Bayesian framework. Information Fusion, Article 102972. https://doi.org/10.1016/j.inffus.2025.102972 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS) (https://doi.org/10.54499/UIDB/04152/2020)